Students’ Awareness of Metacognitive Reading Strategies in Academic Reading - Dangin, Dangin (Journal of English Teaching and Learning Issues, 2020)
Being aware of reading strategies becomes the key of readers’ success in reading process, this study began with its purpose to investigate the readers’ awareness of metacognitive reading strategies while facing academic reading texts. Then, the respondents here were whole 50 students of English department, who had completed the questionnaire of Survey of Reading Strategies Awareness (SORS). Those respondents were intended to reveal the type of reading strategies used during reading academic materials in English. The results of study revealed that those respondents were aware of using two of three categories of reading strategies while reading the materials. As the detail, the results showed that the respondents mostly tended to use the strategies categorized in Problem Solving Strategies (PROB) in order to solve their obstacle in reading.  Global Reading Strategies (GLOB) as second place, which is mostly used by the respondents. And the last or the lowest strategies in use are Support Strategies (SUP).